Actividad analgésica del extracto acuoso liofilizado de las hojas de Bixa orellana L. en ratones albinos - Betancourt B., José (2006)
An experimental research is carried out ain to evaluate the analgesic effect of the lyophilized extract from the Bíxa orellana L leaves, that was administrated by oral via at a 100 and 150 mgkg-l doses. Hot- plate and abdominal contortions methods were applied in the research development. The selected animals were albino male mice from the stock Batb/c-53 at a corporal weight steemed in 23.67 + 1.03g. Paracetamol and indometacina were employed as positive controls at a 400 mgkg-l and 10 mgkg-l doses respectively.According to the obtained results, it concludes that the Bixa orellana L., presents analgesical activity at a peripheric level in the abdominal contortions model, that was directly proportional to the doses under our experimental conditions. .